(untitled) (World Bulletin of Public Health, 2023)
In the structure of patients with acute pancreatitis (AP), patients with pancreatic necrosis (PN) usually account for 15-30%, and 70-80% of them are infected with necrosis foci[1]. Postoperative mortality in GP without differentiation of its clinical forms is 23-26 %, and the proportion of purulent complications among the causes of death in patients with PN reaches 80%